GXMR-CAR containing distinct GXM-specific single-chain variable fragment (scFv) mediated the cell activation against Cryptococcus spp. And had difference in the strength of tonic signaling - Machado, Michele Procópio; dos Santos, Matheus Henrique; Guimarães, Júlia Garcia; de Campos, Gabriela Yamazaki; Brito, Patrícia Kellen Martins Oliveira; Ferreira, Camilly Melo Garcia; Rezende, Caroline Patini; Frota, Natália Fernandes; Soares, Sandro Gomes; Kumaresan, Pappanaicken R.; Lourenzoni, Marcos Roberto; da Silva, Thiago Aparecido [UNESP] (Taylor & Francis, 2023)
Cryptococcus spp. has a polysaccharide capsule composed of glucuronoxylomannan-GXM, a major virulence factor that can prevent the recognition of fungi by immune cells. Chimeric Antigen Receptor (CAR) redirects T cells to target Cryptococcus spp. as previously demonstrated by a CAR specific to GXM, GXMR-CAR. The current study evaluated the strength of the signal transduction triggered by GXMR-CAR, composed of a distinct antigen-binding domain sourced from a single-chain variable fragment (scFv). GXM-specific scFv derived from mAbs 2H1 and 18B7, 2H1-GXMR-CAR and 18B7-GXMR-CAR, respectively, were designed to express CD8 molecule as hinge/transmembrane, and the costimulatory molecule CD137 (4-1BB) coupled to CD3ζ. The 2H1-GXMR-CAR or 18B7-GXMR-CAR Jurkat cells recognized soluble GXM from C. gattii and C. neoformans, and the levels of IL-2 released by the modified cells did not differ between the GXMR-CAR constructs after exposure to Cryptococcus spp. 18B7-GXMR-CAR triggered tonic signaling was more pronounced in modified Jurkat cells, and a protein kinase inhibitor of the Src family (dasatinib) significantly reduced GXMR-CAR tonic signaling and inhibited cell activation against ligands. 18B7 scFv showed a structural modification of the variable heavy (VH) chain that clarified the difference in the strength of tonic signaling and the level of cell activation between 2H1-GXMR-CAR and 18B7-GXMR-CAR. GXMR-CAR constructs induced T-cell activation against clinical isolates of Cryptococcus spp. and serum from patients with cryptococcosis induced high levels of IL-2, mainly in cells modified with 18B7-GXMR-CAR. Thus, 18B7-GXMR-CAR and 2H1-GXMR-CAR mediated T cell activation against Cryptococcus spp. and 18B7 and 2H1 scFv influenced the strength of tonic signaling.